(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Thermal conductivity (denoted as k, j, or k) measures the heat conducting capability of a material. As shown in Fig. 1(a), it can be defined as the thermal energy (heat) Q transmitted through a length or thickness L in the direction normal to a surface area A, under a steady-state temperature difference Th _ Tc. Thermal conductivity of a solid-phase material can span for several orders of magnitude, with a value of _0.015 W=mK for aerogels at the low end to _2000 W=mK for diamond and _3000 W=mK for singlelayer graphene at the high-end, at room temperature. Thermal conductivity of a material is also temperature-dependent and can be directional-dependent (anisotropic). Interfacial thermal conductance (denoted as K or G) is defined as the ratio of heat flux to temperature drop across the interface of two components. For bulk materials, the temperature drop across an interface is primarily due to the roughness of the surfaces because it is generally impossible to have atomically smooth contact at the interface as shown in Fig. 1(b). Interfacial thermal conductance of bulk materials is affected by several factors, such as surface roughness, surface hardness, impurities and cleanness, the thermal conductivity of the mating solids, and the contact pressure 1. For thin films, the temperature drop across an interface can be attributed to the bonding strength and material difference. Note that thermal contact resistance and thermal boundary resistance (or Kapitza resistance 2) are usually used to describe heat conduction capability of an interface in bulk materials and thin films, respectively. Interfacial thermal conductance is simply the inverse of thermal contact/boundary resistance. Knowledge of thermal conductivity and interfacial thermal conductance and their variation with temperature are critical for the design of thermal systems.